Therapeutic benefit of radial optic neurotomy in a rat model of glaucoma - Belforte, Nicolás Adalberto (2012)
Radial optic neurotomy (RON) has been proposed as a surgical treatment to alleviate the neurovascular compression and to improve the venous outflow in patients with central retinal vein occlusion. Glaucoma is characterized by specific visual field defects due to the loss of retinal ganglion cells and damage to the optic nerve head (ONH). One of the clinical hallmarks of glaucomatous neuropathy is the excavation of the ONH. The aim of this work was to analyze the effect of RON in an experimental model of glaucoma in rats induced by intracameral injections of chondroitin sulfate (CS). For this purpose, Wistar rats were bilaterally injected with vehicle or CS in the eye anterior chamber, once a week, for 10 weeks. At 3 or 6 weeks of a treatment with vehicle or CS, RON was performed by a single incision in the edge of the neuro-retinal ring at the nasal hemisphere of the optic disk in one eye, while the contralateral eye was submitted to a sham procedure. Electroretinograms (ERGs) were registered under scotopic conditions and visual evoked potentials (VEPs) were registered with skull-implanted electrodes. Retinal and optic nerve morphology was examined by optical microscopy. RON did not affect the ocular hypertension induced by CS. In eyes injected with CS, a significant decrease of retinal (ERG a- and b-wave amplitude) and visual pathway (VEP N2-P2 component amplitude) function was observed, whereas RON reduced these functional alterations in hypertensive eyes. Moreover, a significant loss of cells in the ganglion cell layer, and Thy-1-, NeuN- and Brn3a- positive cells was observed in eyes injected with CS, whereas RON significantly preserved these parameters. In addition, RON preserved the optic nerve structure in eyes with chronic ocular hypertension. These results indicate that RON reduces functional and histological alterations induced by experimental chronic ocular hypertension.